The Positive Procedural Obligations of States under Article 2 and 3 of the European Convention on Human Rights: Lithuanian Experience - Goda, Gintaras (Teisė, 2021)
The article analyzes the reasons why the ECtHR finds violations of Articles 2 and 3 of the ECHR quite often in cases against Lithuania. The investigation aims to reveal the main mistakes made by the subjects of pre-trial investigation and the courts, which lead to violations of the ECHR.
Keywords: positive state obligations; ECHR; effective investigation of violent events